Association between intraoperative fluid management and post-operative acute kidney injury: A single-center observational study - Rajeshwari K; Irukulla Avanthi (Asian Journal of Medical Sciences, 2024)
Background: Post-operative acute kidney injury (AKI) poses significant risks. Identifying intraoperative determinants is crucial for enhancing patient outcomes and tailoring surgical interventions. Aims and Objectives: This study aimed to investigate the onset of post-operative AKI in patients subjected to various surgical interventions and identify potential intra-operative determinants. Materials and Methods: In this observational investigation conducted at our institution, 100 patients who underwent diverse surgical procedures were included in the study. AKI diagnosis was based on the kidney disease: improving global outcomes guidelines. The parameters assessed encompassed patient demographics, intraoperative fluid management, surgical and anesthetic durations, and post-operative AKI incidence. Determinants of AKI were identified using multivariate logistic regression. Results: The cohort comprised 58% males, with a mean age of 65±12 years. Key comorbidities included hypertension (42%), diabetes mellitus (28%), chronic kidney disease (15%), and cardiovascular disease (20%). Intraoperatively, the average fluid volume administered was 2.5 ± 0.8 L. Fluid management primarily included balanced crystalloids (70%), followed by normal saline (20%), and colloids (10%). Anesthesia was maintained for an average of 3.5 ± 1.2 h. Post-surgery, 15% of the patients developed AKI. A detailed evaluation revealed a strong association between positive intraoperative fluid balance and AKI onset. The statistical analysis pinpointed elevated intraoperative fluid balance (odds ratio: 5.89; 95% confidence interval [CI]: 1.72–20.15; P=0.004) and extended anesthesia duration (odds ratio: 2.12; 95% CI: 1.01–4.47; P=0.046) as significant predictors. Conclusion: AKI onset post-surgery is closely tied to intraoperative factors, notably fluid balance, and anesthesia duration. This underscores the importance of personalized fluid management and vigilant post-operative renal function monitoring to mitigate AKI risks.